Vegetative disbalance correction in metabolic syndrome treatment - E. M. Khurs; A. V. Poddubnaya; O. G. Smolenskaya (Кардиоваскулярная терапия и профилактика, 2010)
Aim. To investigate neuro-vegetative features of cardiovascular regulation in patients with metabolic syndrome (MS); to study the potential of nebivolol in correction of vegetative disbalance among MS patients. Material and methods. This prospective study included 28 untreated patients with MS. All participants received nebivolol (5—10 mg/d) for 6 months. At baseline and 6 months later, bifunctional 24-hour blood pressure (BP) and electrocardiography (ECG) monitoring was performed. Results. After 6 months of nebivolol treatment, a significant reduction in SDANN (p=0,031) was observed, associated with decreased low-frequency (LF) power (р=0,065) and sympatho-vagal LF/HF index (р=0,034). Left ventricular (LV) relative wall thickness also decreased (p=0,002), as well as the prevalence of concentric LV hypertrophy. All patients achieved target BP levels, without any disturbances of lipid and carbohydrate metabolism. Conclusion. In MS patients, nebivolol, as a cardioprotective and metabolically neutral agent, could be effectively used as a regulator of sympathetic influences on heart rate.